Human Security Concept in the UN Practice - Bokeriya, S.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
This article is devoted to the theme, scientific actuality and practical relevance of which is not in doubt, and is caused by a new wave of interest in human security. The human security concept has been the subject of active discussions on national and international security forums for the past 10 years. This article is focused on the human security concept evolution in the framework of the UN in conditions of the growing challenges and threats as well as polycentric world and international relations transformation. The author turned to the analysis of human security issues in the UN human rights dimension, as this organization performs a key role in the application and implementation of the concept on a global scale. The detailed periodization of human security development within the UN is presented for the first time. The analysis of the situation with Syrian refugees in Lebanon is carried out in the format of a case study. Author has made an attempt to undertake not a comprehensive analysis of the concept within the UN, but re-evaluation of new trends and dominant problems in practical application of human security idea and its impact on the effectiveness of international organizations.